THE EFFECT OF USING NAPIER STEM MEDIA ON STUDENTS' UNDERSTANDING OF MATHEMATICAL CONCEPTS - Andrina, Nabila; Nazli, Lira; Pratiwi, Manda Ayu; Sitepu, Melyani Sari; Putri, Dwi Saidah (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2025)
The purpose of this study was to determine the effect of napier rod media on the conceptual understanding of class III SD Negeri 020252 Binjai. This type of research is quantitative. The subjects of the study were all students of class IIIA and IIIB SD Negeri 020252 Binjai. The sampling technique in this study used purposive sampling. The sample in this study amounted to 44 students by taking 2 classes, namely the experimental class and the control class, the experimental class numbered 22 and the control class numbered 22 students. The research instrument used a test. Data analysis techniques include validity test, reliability test, normality test, homogeneity test, n-gain test and hypothesis test. The results showed that napier rod media had an effect on students' conceptual understanding abilities because the results of the t-test analysis (independent t-test) obtained from the results of the significant value (sig.2-tailed) 0.000 0.05, then Ha was accepted and H0 was rejected, meaning that there was an effect of napier rod media on the conceptual understanding of class III students of SD Negeri 020252 Binjai. Students who received treatment using Napier rod media had a higher average when compared to those without using Napier rod media. This means that the variable x (solution) used in the study affects the variable y (problem).